A randomized single-dose, two-period crossover bioequivalence study of two fixed-dose Paracetamol/Orphenadrine combination preparations in healthy volunteers under fasted condition - Cheah, Kit Yee (BMC Pharmacol Toxicol, 2020)
BACKGROUND: Paracetamol/Orphenadrine is a fixed dose combination containing 35 mg orphenadrine and 450 mg paracetamol. It has analgesic and muscle relaxant properties and is widely available as generics. This study is conducted to investigate the relative bioavailability and bioequivalence between one fixed dose paracetamol/orphenadrine combination test preparation and one fixed dose paracetamol/orphenadrine combination reference preparation in healthy volunteers under fasted condition for marketing authorization in Malaysia. METHOD: This is a single-center, single-dose, open-label, randomized, 2-treatment, 2-sequence and 2-period crossover study with a washout period of 7 days. Paracetamol/Orphenadrine tablets were administered after a 10-h fast. Blood samples for pharmacokinetic analysis were collected at scheduled time intervals prior to and up to 72 h after dosing. Blood samples were centrifuged, and separated plasma were kept frozen (− 15 °C to − 25 °C) until analysis. Plasma concentrations of orphenadrine and paracetamol were quantified using liquid-chromatography-tandem mass spectrometer using diphenhydramine as internal standard. The pharmacokinetic parameters AUC(0-∞), AUC(0-t) and C(max) were determined using plasma concentration time profile for both preparations. Bioequivalence was assessed according to the ASEAN guideline acceptance criteria for bioequivalence which is the 90% confidence intervals of AUC(0-∞), AUC(0-t) and C(max) ratio must be within the range of 80.00–125.00%. RESULTS: There were 28 healthy subjects enrolled, and 27 subjects completed this trial. There were no significant differences observed between the AUC(0-∞), AUC(0-t) and C(max) of both test and reference preparations in fasted condition. The 90% confidence intervals for the ratio of AUC(0-t) (100.92–111.27%), AUC(0-∞) (96.94–108.08%) and C(max) (100.11–112.50%) for orphenadrine (n = 25); and AUC(0-t) (94.29–101.83%), AUC(0-∞) (94.77–101.68%) and C(max) (87.12–101.20%) for paracetamol (n = 27) for test preparation over reference preparation were all within acceptable bioequivalence range of 80.00–125.00%. CONCLUSION: The test preparation is bioequivalent to the reference preparation and can be used interchangeably. TRIAL REGISTRATION: NMRR- 17-1266-36,001; registered and approved on 12 September 2017.